Metabolic Reprogramming and Inflammatory Response Induced by D-Lactate in Bovine Fibroblast-Like Synoviocytes Depends on HIF-1 Activity - Quiroga, John; Alarcón, Pablo; Manosalva, Carolina; Teuber, Stefanie; Taubert, Anja; Hermosilla, Carlos; Hidalgo, María Angélica; Carretta, María Daniella; Burgos, Rafael Agustín (Frontiers in Veterinary Science, 2021)
Acute ruminal acidosis (ARA) occurs after an excessive intake of rapidly fermentable carbohydrates and is characterized by the overproduction of D-lactate in the rumen that reaches the bloodstream. Lameness presentation, one of the primary consequences of ARA in cattle, is associated with the occurrence of laminitis and aseptic polysynovitis. Fibroblast-like synoviocytes (FLS) are predominant cells of synovia and play a key role in pathophysiology of joint diseases, increasing the release of proinflammatory cytokines. Increased D-lactate levels and disturbances in carbohydrate, pyruvate and amino acid metabolism are observed in synovial fluid of heifers with ARA-related polysynovitis prior to neutrophil infiltration, suggesting an early involvement of metabolic disturbances in joint inflammation. We hypothesized that D-lactate induces metabolic reprogramming along with an inflammatory response in bovine exposed FLS. Gas chromatography-mass spectrometry (GC-MS)-based metabolomic analysis revealed that D-lactate disrupts metabolism of bovine FLS, mainly enhancing glycolysis and gluconeogenesis, pyruvate metabolism and galactose metabolism. RT-qPCR analysis revealed an increased expression of metabolic-related genes, including HIF-1α, Glut-1, L-LDH(A) and PDK-1. Along with metabolic disturbances, D-lactate also induced an overexpression and secretion of IL-6. Furthermore, inhibition of HIF-1, PI3K/Akt and NF-κB reduced IL-6 expression and metabolic-related genes. Our results reveal a potential role for D-lactate in bFLS metabolic reprogramming and support a close relationship between inflammation and metabolism in cattle.